Motivasi Mengajar Tumbuh dari Meaning of Work yang Dirasakan Guru - Azalia Putri Salsabila; Adnani Budi Utami; Sayidah Aulia'Ul Haque (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract This study aims to determine the relationship between the meaning of work and the work motivation of elementary school teachers, particularly during the enjoyable transition period from early childhood education to elementary school. During this phase, teachers are required to create an adaptive, supportive, and enjoyable learning environment for children who have just entered elementary school. Teachers' acceptance of the meaning of their work is an important factor in encouraging their work motivation. This study employs a quantitative approach using correlational techniques. The research subjects are 82 first-grade elementary school teachers involved in the student transition process from preschool to elementary school. The research instruments consist of scales measuring the meaning of work and work motivation. Data were analyzed using Spearman Brown correlation techniques. The results of the study indicate a positive and significant relationship between the meaning of work and teachers' work motivation. The higher the meaning teachers perceive in their work, the higher their work motivation. This finding underscores the importance of strengthening the meaning of work in enhancing teachers' work motivation during this critical transition phase. Keywords: elementary education; elementary school teachers; meaning of work; work; transition from preschool to elementary school; work motivation Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara meaning of work dengan motivasi kerja guru sekolah dasar khususnya pada masa transisi menyenangkan dari PAUD ke SD. Pada fase ini, guru dituntut untuk menciptakan lingkungan belajar yang adaptif, mendukung, dan menyenangkan bagi anak-anak yang baru saja memasuki jenjang sekolah dasar. Penerimaan guru terhadap makna pekerjaannya menjadi faktor penting dalam mendorong motivasi kerja mereka. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik korelasional. Subjek penelitian adalah 82 guru kelas 1 sekolah dasar yang terlibat dalam proses transisi siswa dari pembelajaran anak usia dini ke sekolah dasar. Instrumen penelitian berupa skala meaning of work dan motivasi kerja. Data dianalisis dengan menggunakan teknik korelasi Spearman Brown. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara meaning of work dan motivasi kerja guru. Semakin tinggi makna yang dirasakan guru terhadap pekerjaannya, semakin tinggi pula motivasi kerjanya. Temuan ini menegaskan pentingnya penguatan makna kerja dalam meningkatkan motibasi kerja guru selama fase transisi penting ini. Kata kunci: guru sekolah dasar; meaning of work; motivasi kerja; pendidikan dasar; transisi PAUD ke SD